The Effect of Discovery Learning Model on Concept Mastery and Critical Thinking Ability of Biology Students - Baiq Wahdini Yutama Sari; A Wahab Jufri; Anindita SHM Kusuma (Postgraduate, University of Mataram, 2024)
This study aims to analyze the effect of the application of the discovery learning model on concept mastery and critical thinking skills of biology students in class X SMA Negeri 2 Labuapi. The classes that were used as samples were first tested for equality in all X classes using a multiple choice test and then analyzed using the costat test so that class XD was obtained as the experimental class and class XA as the control class. Data collection on concept mastery used multiple choice tests while data on critical thinking skills used essay tests. Data analysis used anacova test with a significance value of concept mastery obtained of 0.001 (significant <0.05). The significance value of critical thinking ability obtained was 0.002 (significant <0.05). The results showed that 1) there is an effect of the discovery learning model on the mastery of concepts of students in class X SMA Negeri 2 Labuapi and 2) there is an effect of the discovery learning model on the critical thinking skills of students in class X SMA Negeri 2 Labuapi.